Meat origin differentiation by polymerase chain reaction-restriction fragment length polymorphism. Issue 1 (1st January 2021) - Islam, Ariful; Halder, Joyanta; Rahman, ATM Mijanur; Ud-Daula, Asad; Uddin, Salah; Hossain, Mridha Kamal; Jahan, Nusrat; Alim, Abdul; Bhuyan, Anjuman Ara; Rubaya,; Hasan, Mahmud; Alam, Jahangir
ABSTRACT: Identification of meat and meat products is significant for economic, religious, or public health reasons. This study focused on the detection and differentiation of meat animal species. A total of sixty-four meat samples (10 samples of each like beef, buffen, chevon, and mutton; twenty-four samples of pork) were analyzed for these purposes. PCR-RFLP of 12S rRNA gene with four restriction enzymes was performed on individual meat samples as well as mixture of different meat. Species specific primers as well as sequencing of DNA were also used to detect and verify the RFLP results. PCR amplification yielded a 456bp fragments from 100% samples. Alu I digested beef DNA into 359 and 97bp, chevon and mutton DNA into 246 and 210bp fragments and pork DNA into 290 and 166bp fragments. However, it cannot digest buffen DNA. On the other hand Hha I digested only buffen DNA into 247 and 209bp fragments but not others. Apo I restricts only mutton DNA and yielded 329 and 127bp fragments but not others. Nevertheless, BspT I yielded 323 and 133bp fragments only from chevon. Besides, mixed samples (1:1) of beef-buffen and chevon-mutton can be differentiated by Alu I & Hha I and BspT I & Apo I, respectively. Chord analysis based on our sequence and respective sequences of studied animals from GenBank indicated that the cutting sites are conserved in these species of animals. Phylogenetically each of the species was clustered separately. This technique may be useful for meat animal species detection and differentiation either from individual meat and mixed meat samples.